Pengaruh Gaya Hidup Dan Kelompok Referensi Terhadap Keputusan Pembelian Smartphone Merek Xiaomi (Studi Empiris Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Unisma) - Muhammad Sulton; Budi Wahono; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2021)
Abstract :This study looks for the influence of lifestyle and reference groups on the purchase decision of Xiaomi at the Faculty of Economics and Business, UNISMA 2016 class. This research is quantitative in nature which aims to find significant influence partially and simultaneously. The number of respondents used was 75 respondents, all of whom were S1 students of the Faculty of Economics and Business UNISMA class 2016. This research method was tested by validity and reliability tests. The classical assumption test used is the normality assumption test, multicollinearity assumption test, and heteroscedasticity assumption test. In addition, multiple linear regression tests are also used, and hypothesis testing, namely the F test, T test, and determination test (R2). The results of this study indicate that there is a significant influence simultaneously between lifestyle variables and the reference group on purchasing decisions. Partially, there is a significant influence of lifestyle on purchasing decisions, and the reference group has a significant effect on purchasing decisions. Lifestyle is the most dominant variable in purchasing decisions for Xiaomi at the 2016 Faculty of Economics and Business UNISMA.Keywords: Lifestyle, Reference Group, Purchase Decision